If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 117 + -7x = 38x + 22 Reorder the terms: 117 + -7x = 22 + 38x Solving 117 + -7x = 22 + 38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38x' to each side of the equation. 117 + -7x + -38x = 22 + 38x + -38x Combine like terms: -7x + -38x = -45x 117 + -45x = 22 + 38x + -38x Combine like terms: 38x + -38x = 0 117 + -45x = 22 + 0 117 + -45x = 22 Add '-117' to each side of the equation. 117 + -117 + -45x = 22 + -117 Combine like terms: 117 + -117 = 0 0 + -45x = 22 + -117 -45x = 22 + -117 Combine like terms: 22 + -117 = -95 -45x = -95 Divide each side by '-45'. x = 2.111111111 Simplifying x = 2.111111111
| (x^2-1)*(2*x-2)-(x^2-2*x+1)*(2*x)=0 | | 8-(4x-2)=2(8x-5) | | 200-6x=30x+24 | | 9x+3=5x-9 | | 6w-6=12 | | x^2+2x-xy-2y=0 | | 7-7x=103-35x | | -130-9x=8x+23 | | x^2=(3+4) | | 2y+5=8y+10 | | -9+9y+2-3y= | | 115-6x=2x+19 | | 12x+40=4 | | 5x+58=3 | | 6x^2-864=0 | | 9x-23=22 | | -9+9z+4-7z= | | 7m-17=32 | | 2m+16=5m+4 | | 40y+40=50y+50 | | -2(x+3)+3x=13 | | 6y+3=y-7 | | 6y+3y=8y-6 | | 22-4x=-8x+2 | | 6t-t-4=4t-6 | | (7x+2)(5x-4)=0 | | 105+9=49 | | 4b-0.9=5b | | 12-b=3b-16 | | 43-4x=5x-23 | | -12+b=3b+32 | | x+3x+15=91 |